GREEKS’ INTENTIONS TO VISIT A GREEN HOTEL ARE INFLUENCED BY PERCEIVED CONTROL AND PAST EXPERIENCE - ANTONIA DELISTAVROU; IRENE TILIKIDOU (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
This research study addressed the ability of an extended with Past Experience model of the Theory of Planned Behavior (TPB) to reveal the Greek travelers’ intentions to choose a green hotel over a conventional one. Perceived Behavioral Control provided a stronger impact on intentions, followed by Subjective Norms and Past Experience, while Attitudes offered rather weak evidence of influence. The additional factor of Past Experience was found to be also correlated with Perceived Behavioral Control. Therefore, it can be implied that green hotels’ communication strategies should firstly underline the travelers’ own control to choose a green hotel, emphasizing that there are no time, money, or opportunity obstacles to restrict them. Secondly, visitors as well as distinguished persons, who have previously experienced a visit to a green hotel, should be promoted and valorized in an effort to increase social pressure. Thirdly, staying at a green hotel should be presented as a positive, environmentally beneficial while healthy, desirable, and enjoyable experience.